Quality of Life in Mothers With Perinatal Depression: A Systematic Review and Meta-Analysis - Li, Jiaying; Yin, Juan; Waqas, Ahmed; Huang, Zeyu; Zhang, Hongji; Chen, Manqing; Guo, Yufei; Rahman, Atif; Yang, Lei; Li, Xiaomei (Frontiers in Psychiatry, 2022)
Background: The prevalence of perinatal depression is high and its adverse effects on mothers and infants are extensive. Several studies have explored the relationship between perinatal depression and health-related quality of life (HRQoL), but little is known about the nature and magnitude of this effect. The objectives of this study were to evaluate the HRQoL of mothers with perinatal depression and compare the HRQoL of depressed mothers with that of non-depressed mothers. Methods: A systematic review was performed according to the PRISMA guidelines. PubMed, EMBASE, Scopus, PsycINFO, Web of Science, Cochrane Central Register, the China National Knowledge Infrastructure, the VIP Database, and the Wan Fang Database were searched. The retrieval time was from the establishment of the database to July 2020. A series of meta-analyses were run for each outcome pertaining to HRQoL sub-measures. Subgroup analyses were conducted based on country income category and time period. Results: Of 7945 studies identified, 12 articles were included in the meta-analysis, providing HRQoL data for 4392 mothers. Compared with non-depressed mothers, mothers with perinatal depression reported significantly poor scores across all the quality-of-life domains. Mixed-effects analysis showed that there was no difference in the HRQoL scores of mothers with antepartum and postpartum depression. Mothers with perinatal depression in higher-income countries reported higher disability on role-physical (p=0.02) and social functioning domains (p=0.001) than those from lower-income countries. Limitations: Due to insufficient data, no regression analysis was performed. The inability to accurately determine the difference in HRQoL between antepartum and postpartum depression was because of the restriction of the included studies. Moreover, most of the included studies were conducted in middle-income countries and may have an impact on the applicability of the results. Subgroup analyses are observational and not based on random comparisons. The results of subgroup analyses should be interpreted with caution. Conclusion: HRQoL is compromised in mothers with perinatal depression. Continuous efforts are required to improve the HRQoL of perinatal depressed mothers.